Univalence Conditions Related to a General Integral Operator - Nicoleta Breaz; Virgil Pescar (Abstract and Applied Analysis)
We consider a general integral operator based on two types of analytic functions, namely, regular functions and, respectively, functions having a positive real part. Some univalence conditions for this integral operator are obtained.